Blockade Effects of Anti-Interferon- (IFN-) γ Autoantibodies on IFN-γ-Regulated Antimicrobial Immunity - Dyah Ika Krisnawati; Yung-Ching Liu; Yuarn-Jang Lee; Yun-Ting Wang; Chia-Ling Chen; Po-Chun Tseng; Ting-Jing Shen; Chiou-Feng Lin (Journal of Immunology Research)
The interferon- (IFN-) γ expression is elicited in response to microbial infections and activates immune surveillance by antimicrobial immune elements to induce microbial killing. Patients with adult-onset immunodeficiency who suffer from recurrent infections with microbes, particularly nontuberculous mycobacteria (NTM), commonly display genetic defects in IFN-γ signaling as well as the generation of anti-IFN-γ autoantibodies (autoAbs). Because IFN-γ is an activator of macrophage differentiation and a proinflammatory activator of innate immunity, the blockade effects of the autoAbs present in NTM patient serum on IFN-γ are hypothesized to regulate the antimicrobial function of macrophages. In the presence of patient serum, IFN-γ-induced type 1 macrophage (M1) differentiation was inhibited in PMA-stimulated human monocytic THP-1 cells. Treatment with patient serum significantly blocked the production of proinflammatory factors, including cytokines/chemokines and reactive oxygen/nitrogen species, by M1 macrophages. Importantly, IFN-γ-facilitated phagocytosis and degradation of heat-killed mycobacterium were decreased by cotreatment with patient serum. These results show the blockade activity of anti-IFN-γ autoAbs on IFN-γ-mediated antimicrobial immunity in macrophages.